Analysis of Risk-Taking Policy Channel on Indonesian Banking Performance - Ferdy Gerry Ramadhan; Benardin (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
The purpose of this research is to explore how monetary policy influences the risk-taking of banks performance in Indonesia. The study measures the risk-taking policy channel, which is the way that monetary policy affects the risk preferences and actions of banks. The study uses five indicators: ROA, FDR, OER NPL, and M2. The study applies VECM to examine the date  from 2010 to 2021. The findings reveal that Variables ROA, FDR AND OER have short-run and ROA, NPL, M2, and FDR correlated with each other in the long run. The findings also show OER is only significantly correlated with M2 in the long run, this means that loose monetary policy lowers the profitability, liquidity, and efficiency of banks, and raises the credit risk. Efforts that can be made by management to improve bank performance is to increase efficiency operations, controlling credit risk, and anticipating market risk. Bank operational costs must be suppressed by maximizing resources owned, so should credit risk suppressed by improving credit quality through tightening credit standards, and market risk can be anticipated by maximizing the spread through determining loan interest rates competitive. The capital market in Indonesia is Capital markets are at a developing level (emergency market), so the opportunity to implement this policy is quite open.